THE INFLUENCE OF SELF-DEVELOPMENT, POTENTIAL, AND POLICY ON THE COMPETENCE OF PE TEACHERS - Ramadhan, Ilham; Alnedral, Alnedral; Welis, Wilda; Zulbahri, Zulbahri (STKIP Singkawang, 2024)
PE (Physical Education) teachers play a role in shaping students who are physically and mentally healthy, and social. Adequate teacher competence is needed, although challenges such as self-development, technology utilization, and policy support still exist. This study analyzes the influence of self-development, potential, and educational policies on the competence of PE teachers in Pasaman Barat using the Structural Equation Modeling (SEM) method. The results showed that self-development had a significant effect on teacher competence with a coefficient of 0.585 and also increased teacher potential (coefficient 0.765). Potential plays a role as a mediation variable with a significant influence (0.442) on competence. However, education policy did not show a significant direct influence on competence (coefficient 0.015) but contributed to an increase in potency (0.119). These findings emphasize the importance of continuous self-development programs and more effective policy support to improve the competence of PE teachers.